Answer:
u = -4 or -6
Explanation:
We know that,
( a + b ) = a² + 2ab + b²
Accordingly, let us solve the given equation.
( u - 1 )² = 2u² + 8u + 25
First, solve the brackets.
u² - 2u + 1 = 2u² + 8u + 25
Subtract u² by both sides.
-2u + 1 = 2u² - u² + 8u + 25
-2u + 1 = u² + 8u + 25
Now, add 2u by both sides.
1 = u² + 8u + 2u + 25
Subtract 1 by both sides.
0 = u² + 10u + 25 -1
0 = u² + 10u + 24
And solve the quadratic equation and solve for u.
0 = u² + 6u + 4u + 24
0 = u ( u + 6 ) + 4 ( u + 6 )
0 = ( u + 4 ) ( u + 6 )
Therefore,
u + 4 = 0
u = -4
or
u + 6 = 0
u = -6